The Requerimiento in the Old World: Making Demands and Keeping Records in the Legal Culture of Late Medieval Castile. (February 2022) - Israeli, Yanay
Abstract : This article analyses the place of the legal procedure known as requerimiento (requirement) in the social life of late medieval Castile. Drawing on archival sources from the fourteenth and fifteenth centuries, it examines how Castilians deployed the requerimiento and what meanings and functions this procedure assumed, particularly in processes of conflict-management. While much has been written about the requerimiento as a ritual of conquest in Spanish America, the place of this procedure in the legal culture of late medieval Castile has received little scholarly attention. By examining how the requerimiento operated within the world of civic disputes in Castilian villages and towns, this study brings to light a rather unknown background for the more familiar requerimiento, the colonial ritual of the sixteenth century.